PENGGUNAAN SOLAR SELL PADA POMPA AIR DC 12 V SUBMERSIBLE 280 W UNTUK SUMUR BOR 30 M - Sariman Sariman; M. Fauzan Deyhan (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Drilling wells are a way of extracting groundwater by sticking pipes into the ground to a certain depth. The purpose of this study is to analyze the energy performance of solar cells to operate water pumping machines in drilled wells, with the results of the analysis and design that are appropriate, then these needs can be fulfilled. The research method used is the development research method, namely developing the use of solar cells in submersible E 280W DC 12 V water pumps for 30 M drilled wells. The research site was conducted in Limbang Jaya Village, Tanjung Batu District, Ogan Ilir Regency. The research will be carried out in August 2022. The tools used are deep well drilling machines, drill pipes, drill bits, traveling blocks, water swivels, drill towers, and hoisting plugs. The effect of depth on DHL in dug wells is only 4% while the distance from the shoreline does not affect DHL in dug wells, the effect of depth on DHL in drilled wells is 37%.